THE EFFECT OF PARENTAL ATTENTION ON MATHEMATICS LEARNING OUTCOMES IN GRADES X AND XI STUDENTS OF SMK KHAMAS ASEMBAGUS - Lisma Dian Kartika Sari; Nur Hasanah; Buaddin Hasan; Ida Fitriana Ambarsari (Journal on Research and Review of Educational Innovation, 2023)
One of the external factors that can affect student learning outcomes is the family environment, in this case, the attention of parents. Research has been carried out to determine whether or not there is an influence of parental attention on student learning outcomes in mathematics. This research is a quantitative study using the Ex-Post Fact method . Sampling was carried out using a probability sampling technique of the simpler random type which was carried out on 111 respondents consisting of class X and XI at SMK Khamas Asembagus. Data collection techniques used are observation, documents and questionnaires. The results showed that 0.237 > 0.1865 at Cronbach's Alpha = 0.1865, this indicates that the instruments used in this study are valid and reliable. Meanwhile, the results of the T test were 2.545 > 1.65895 (with ) and the Effectiveness of the Regression Line (EGR) was 3.25% which indicated that there was an influence of parental attention on student learning outcomes in Mathematics Subject of 3.25%. Based on the results of the analysis of research data, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H 0 ) is rejected, meaning that there is an influence between parents' attention to student learning outcomes in Mathematics Subject which is equal to 3.25%.